Residual Power Series Method for Solving Klein-Gordon Schrödinger Equation - Manaa, Ssaad A.; Easif, Fadhil H.; Murad, Jomaa J. (Science Journal of University of Zakho, 2021)
In this work, the Residual Power Series Method(RPSM) is used to find the approximate solutions of Klein Gordon Schrödinger (KGS) Equation. Furthermore, to show the accuracy and the efficiency of the presented method, we compare the obtained approximate solution of Klein Gordon Schrödinger equation by Residual Power Series Method(RPSM) numerically and graphically with the exact solution.